Decreased Bilirubin is Associated With Disease Activity of Primary Sjögren’s Syndrome - Jing XIE; Zhencheng ZHANG; Yan LIANG; Zaixing YANG (Archives of Rheumatology, 2020)
Objectives: This study aims to determine the serum bilirubin levels in primary Sjögren’s syndrome (pSS) patients and to explore clinical significance of bilirubin in pSS. Patients and methods: Retrospective analysis of electronic medical records was performed in 97 pSS patients (12 males, 85 females; mean age 54±15 years; range, 15 to 91 years) and 100 healthy controls (17 males, 83 females; mean age 51±14 years; range, 25 to 75 years). Serum bilirubin and other variables were compared between pSS patients and healthy controls. The European League Against Rheumatism Sjögren’s syndrome disease activity index (ESSDAI) was used to assess the disease activity of pSS, and ESSDAI ≥5 was defined as moderate to high activity. The relationship between bilirubin and ESSDAI was analyzed by Spearman’s correlation analysis and multivariable logistic regression. Results: The median level of serum bilirubin was 9 μmol/L (interquartile range (IQR), 7-13 μmol/L) in pSS patients, much lower than healthy controls (median, IQR, 13, 10-18 μmol/L) (p<0.001). It was positively correlated with age (r=0.255, p=0.012), but negatively with immunoglobulin (Ig) A (r=-0.314, p=0.003), IgG (r=-0.265, p=0.015), erythrocyte sedimentation rate (r=-0.309, p=0.002) and ESSDAI (r=-0.342, p=0.001). Multivariate analysis revealed that increased bilirubin was independently associated with decreased risk of moderate to high disease activity (odds ratio, 95% confidence interval: 0.852, 0.730-0.955). Conclusion: Serum bilirubin is decreased in pSS patients and may be a useful biomarker for reflecting pSS disease activity.